INTEGRASI NILAI ISLAM DAN BUDAYA LOKAL DALAM DAKWAH KULTURAL DI NUSANTARA - M. Shofa A Rosyid; Mulyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the global discourse of religious and cultural studies, the integration of religious values and local culture is regarded as a strategic approach to developing contextual, inclusive, and sustainable da‘wah practices within multicultural societies. Islam, as a universal religion, possesses an adaptive capacity to engage with social and cultural diversity without compromising its essential teachings. In the Nusantara context, the historical spread of Islam demonstrates the success of cultural da‘wah through the internalization of Islamic values into local traditions, resulting in a form of Islam characterized by moderation, civility, and tolerance. Previous studies have examined the relationship between Islam and local culture, the concept of Islam Nusantara, and various practices of cultural da‘wah. However, most of these studies remain largely descriptive and have not comprehensively conceptualized the integration of Islamic values and local culture as a strategic and relevant da‘wah model for contemporary society. Consequently, a research gap persists regarding the understanding of cultural da‘wah as a strategic framework capable of bridging normative Islamic values and socio-cultural realities. This study aims to analyze the concept of integrating Islamic values and local culture within cultural da‘wah in the Nusantara context and to explain its significance as an adaptive da‘wah strategy in plural and multicultural societies. The findings of this study are expected to contribute to the development of da‘wah studies and the advancement of contextual Islamic scholarship.